An Evaluation of the Usefulness of Explanation in a CBR System for Decision Support in Bronchiolitis Treatment - Doyle, Donal; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 2006)
The research presented here explores the hypothesis that the deployment and acceptance of decision support systems in medicine will be enhanced if the basis for the recommendation produced by the system is apparent. We describe a decision support system for advising on patients suffering from bronchiolitis. This system supports its recommendations with precedent cases selected to support the recommendation along with justification text that highlights aspects of these cases relevant to the query case. It also presents an estimate of its confidence in the recommendation. The main contribution of this paper is an evaluation of this system in a clinical context. The evaluation shows that this type of explanation does enhance the usefulness of the system for practitioners.
Keywords: Computer Science